PENDUGAAN PRODUKTIVITAS PADI SAWAH BERDASARKAN REFLEKTANSI (INDEKS VEGETASI), WARNA DAN KERAPATAN TANAMA - Suhardi Suhardi; Daniel Useng; Nugrah Pratiwi Johan (Jurnal Penelitian dan Pengembangan Agrokompleks, 2018)
Production of paddy in a different place is caused by several factors such as soil type, soilnutrient content, pests and diseases, climate change and cultivation techniques. Because ofthese differences, to find out the productivity of land in a large area needs technology so thatthe results are more appropriate. For this reason, this study was conducted with the aim ofestimating land productivity using technology that reflects plant reflectance in several croppingpatterns. , taking a portrait of land appearance and measuring grain productivity to be used asvalidation data. The data is processed by linking reflectance (vegetation index), color, plantdensity and productivity of paddy rice in the same area. The results show that there is arelationship between plant density with the productivity of paddy fields (tons/ha) with acoefficient of determination (R2) that is 0.7. Rice plants in Legowo 2-1 cropping pattern havemore influence on the index increase compared to the Tegel planting pattern. The relationshipbetween the vegetation index and rice productivity (tons/ha) is weak in SR, NDVI, SAVI, MSAVI,and IPVI and is strong in RDVI